Real interest rates, bank borrowing, and fragility - Toni Ahnert; Kartik Anand; Philipp Johann König (Deutsche Bundesbank, 2022)
How do real interest rates affect financial fragility? We study this issue in a model in which bank borrowing is subject to rollover risk. A bank's optimal borrowing trades off the benefit from investing additional funds into profitable assets with the cost of greater risk of a run by bank creditors. Changes in the interest rate affect the price and amount of borrowing, both of which influence bank fragility in opposite directions. Thus, the marginal impact of changes to the interest rate on bank fragility depends on the level of the interest rate. Finally, we derive testable implications that may guide future empirical work.
Keywords: G01; G21; G28; 330; bank borrowing; rollover risk; fragility; real interest rates; global games; funding liquidity risk channel